Processes of urban reorganization and natural hazard levels in a city of middle size: La Serena, Chile - Ortiz Véliz, Jorge; Castro Correa, Carmen Paz; Escolano Utrilla, Severino (Investigaciones Geográficas, 2002)
The urban research in Latin America has been concentrated on the top cities of the national settlement system. Among the issues of research are the social spatial effects, environmental and functional effects and particularly those referred to unequal, segregated and sprawl urban growth. The former issues mentioned are thought to be present in other cities as well, particularly in middle size cities of the urban systems thus playing an important role on spatial structuring at regional scale. The present paper main contribution refers to increasing the knowledge of the changing processes of Chilean middle sizes cities at a regional scale context. The specific study area is the capital city of Coquimbo region named La Serena. It is located in the northern central part of Chile. Recent research results show that this city tends to reproduce largest cities structuring and spatial processes, as well as the modification of population distribution density model, centrality structures, urban sprawl growth and social segregation increasing.